The Determinants of Financial Distress in the Pre Covid-19 Era in Nigeria - Endurance Omovigho Eyamu; Felicia Ogheneotegiri Eyamu; Efemena Otejiri Oliogu (CV. Proaksara Global Transeduka, 2025)
The research investigated the factors influencing financial trouble in Nigeria before the outbreak of COVID-19. The main focus of the study was on financial instability, which was measured using the Altman Z-score. Various factors contributing to financial distress, such as profitability, loan loss provision, liquidity ratio, asset quality, and capital adequacy ratio, were taken into consideration as explanatory variables. Data from the Central Bank of Nigeria's statistical bulletin and the Nigerian Deposit Insurance Corporation's annual report from the years 1992 to 2022 were collected for analysis. The data was then examined using various techniques such as descriptive analysis, correlation analysis, and granger causality test. The E-view software package was utilized to assess the relationship between the explanatory and explained variables in the study. The result shows that profitability (ROCE), loan loss provision (LLP) and liquidity ratio (LIR) are negatively correlated with Altman Z-score and that such relationship is moderate and Asset quality ratio (ASQ) and Capital adequacy (CAR) are positively correlated with Altman Z-score. The study recommended that beyond thinking of profitability, the bank should imbibe efficient and effective management team that will reduce the environmental shocks that affects performance of the Nigerian banking industry. Furthermore, there is need for regulators of the Nigerian banking industry to reexamine the rising of non-performing loans (NPL) occasioned by inability of the deficit economic unit to service their loans.